Structured Training for Enhancing Science Teachers' Competence in Authentic Assessment Design Based on Local Wisdom - Ellianawati Ellianawati; Wiwi Isnaeni; Pratiwi Dwijananti; Ian Yulianti; Bambang Subali; Imelda Laelan Safina; Tutut Arrum Hardianti Ningsih; Agus Kurniawan; Dian Norma Aprillia; Doddy Ardiansyah (Jurnal Abdimas, 2026)
Assessment is an essential part of the learning process because it measures progress toward learning objectives. One type of assessment suitable for today’s learning needs is authentic assessment, which assesses students’ competencies in a real-world context. However, many teachers still lack the skills to develop authentic assessments. Therefore, training activities are needed to help teachers improve their ability to design authentic assessments. To overcome this problem, a structured training program on developing authentic assessments integrated with local wisdom was conducted. This approach was chosen because local wisdom is closely related to students’ daily lives and helps them understand science concepts more easily. The training was carried out using three main strategies: (1) identifying learning objectives and local wisdom potential, (2) formulating competency achievement indicators, and (3) developing authentic assessments. The results of these training activities show positive outcomes. Based on questionnaire responses at the end of the training, the program helped teachers develop and refine authentic assessments that are more contextually relevant and meaningful.